Teknologi Sensor yang Dapat Digunakan dalam Pencegahan Low Back Pain di Kalangan Perawat - Pasti Kurnia; Liya Arista; Tuti Herawati (Journal of Telenursing (JOTING), 2023)
This study aims to discuss various sensor technologies that monitor lumbar, leg, and arm movements, which are considered to contribute to the risk of LBP. The research method used is the literature review method of 10 journals obtained from the EBSCO database, Pro Quest, and EMBASE. The research results were based on the online search method and selection of scientific journals; ten articles were selected for further review. The results of a study of 10 journals show that the sensor technology that has been developed can detect movements of the lumbar, arms, and legs which are effective in evaluating the activities of nurses for the prevention of low back pain. In conclusion, the use of sensor technology that can be used is very efficient. It benefits in increasing nurses' awareness of preventing LBP risks while working. Keywords: Low Back Pain, Sensor Technology, Nurse